PENGUASAAN KONSEP SISWA KELAS XI PADA PEMBELAJARAN SIFAT-SIFAT KOLOID MENGGUNAKAN METODE DISCOVERY-INQUIRY - Masruroh, Kuni Hidayatal (2013)
Discovery-inquiry method is based on a discovery made by the students, the study chose the title "Concept Mastery of Student Grade XI in Learning Attributes Colloidal Using Discovery-Inquiry Method". The research method used is a quasi-experiment with design study is pretest-posttest control group design. Subjects were students of class XI one of the high schools in the Bandung city, as many as 30 students of experiment class and 30 students of control class. The research instrument in the form of a written test questions and interview guides. Based on data analysis, the average value of N-Gain for experimental class is 80.55% and for grade control is 76.2%, the average value of N-Gain include high criteria for the experimental class and control class. For each category of student groups, obtained information that a group of high, medium, low and have mastery of concepts very well with the percentage of the average post-test respectively for 95.32%, 91.88% and 88.88%. Based on mastery of the concepts to each indicator, the indicator got that one study describes the nature of colloids and colloidal properties mentioned have a level mastery of the concept with the excellent category. For indicators of learning classifies various natural phenomena related to the different nature of the colloids have a level mastery of the concept of good category. Based on this research, the learning material properties of colloids using the discovery-inquiry known to make students have a good mastery of the concept.